BIBLIOMETRIC ANALYSIS ON ISLAMIC ENDOWMENT FUNDS (WAQF) FOR SUPPORTING SDGs 1 - Ramdani, Ramdani; Ma’ruf, Aminudin (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Waqf research was started in 1914. Since then, the term "waqf” has been popular among researchers who want to learn more. This research aims to examine the scholarly literature on the topic of waqf supporting SDGs 1. The Scopus database was used to compile all waqf literature. The data was incorporated using the Publish or Perish software, and the data were analysed using Microsoft Excel. Standard bibliometric analysis was used to show the rise of publications, research productivity, and citation analysis. After deleting certain documents that were unrelated to the issue, a total of 464 documents were retrieved based on the search results. Since 2017, the rate of expansion of waqf literature has accelerated dramatically. The majority of the publications were written in English and published in journals and conferences. Malaysia was the site of the majority of Waqf research. This study examines the evolution of the scientific literature in the field of waqf and identifies areas of current academic interest and prospective research objectives.